Catch Basin Insert: Characterization and Modelling of Stormwater Treatment at Source - Alam, Md Zahanggir (Curtin University, 2018)
This research investigates the hydraulics of catch basin insert (CBI) for treating stormwater at source. Field and laboratory investigations checked the solid removal capacity of geotextiles in CBI. Laboratory experiments also conducted to check the nutrient removal capacity of biochar and alum sludge. A modified CBI is proposed with two chambers. The upper chamber with geotextile basket will capture gross pollutants and lower chamber with adsorbent material will remove nutrients and thus produce cleaner stormwater.